Quick Reference Guide to the Worker Protection Standard (WPS) as Revised in 2015 - Frederick M. Fishel (EDIS, 2017)
This 8-page document provides a summary, including the 2015 revisions, of the Federal Worker Protection Standard. For the full details, please refer to the EPA's How to Comply Manual. Written by Frederick M. Fishel and published by the UF Agronomy Department, January 2017.